Optimization of milling carbon fiber reinforced plastic using RSM - Muhamad Khairussaleh, Nor Khairusshima; A.K., Nurul Aqella; Syed Shaharuddin, Sharifah Imihezri (Elsevier, 2017)
Carbon Fibre Reinforced Plastic (CFRP) is extensively used nowadays especially in the industries due to its desirable properties of high strength, light weight and high resistance to corrosion. However, the machining of CFRP composites requires great specification and requirement as it is difficult to be machine. Besides, improper technique and parameters used to machine CFRP may result in poor surface quality such as high surface roughness and delamination. This study was done on a CFRP panel with solid uncoated carbide tool with diameter of 8 mm was used as cutting tool. Thus, this project investigates the influence of the cutting parameters which are spindle speed, feed rate and depth of cut to the surface quality of the CFRP by undergoing milling operation. The cutting parameters used during the milling operation of the CFRP panel ranged from 500 rpm to 3500 rpm for the cutting speed, feed rate from 100 mm/min to 900 mm/min and lastly 0.5 mm to 2.0 mm range for depth of cut. 15 runs of experiments is performed based on the Central Composite Design (CCD) of Response Surface Methodology. Through this study, the optimum cutting parameters during milling of CFRP is determined and the main factors affecting the surface quality are also highlighted. Based on the developed mathematical model, the feed rate was identified as the primary significant parameter that influenced surface roughness and delamination. In conclusion, the influence of the cutting parameters on the CFRP panel is higher cutting speed, lower feed rate and lower depth of cut resulted in low surface roughness and delamination factor. Feed rate was identified to be the primary significant cutting parameter that contributes to low surface roughness and delamination factor. The optimized cutting parameters were cutting speed, feed rate and depth of cut of 3061 rpm, 211.34 mm/min and 0.72 mm respectively with surface roughness of 1.34 um and delamination factor of 1.08.